COMPARATIVE FLORAL ANATOMY AND DEVELOPMENT IN NEOTROPICAL LAURACEAE - Graca Sajo, M. [UNESP]; Moraes, Pedro L. R. [UNESP]; Assis, Leandro C. S.; Rudall, Paula J. (Univ Chicago Press, 2016)
Premise of research. The pantropical magnoliid family Lauraceae has an extensive macrofossil record that dates back to the Early Cretaceous. However, flower anatomy among extant species is relatively poorly known. We investigate flower structure and development in six Neotropical genera to elucidate the homologies of the floral parts, especially the prominent appendages that occur on the filaments of the inner fertile stamen whorl in some species. Methodology. We used SEM and LM to examine flower organization and development in 11 species of six genera (Aniba, Cryptocarya, Endlicheria, Licaria, Nectandra, Ocotea) and flower vasculature in two species (Cryptocarya moschata and Ocotea prolifera). Pivotal results. All the flowers examined are typical of Lauraceae: they are very small and possess two whorls of tepals that are similarly vascularized, with three bundles each (resembling bracteopetals), multiple androecium whorls, and a single carpel. Variation exists in some characters, especially in the androecium. A fourth (innermost) androecial whorl is present as staminodia in some species. The prominent stamen appendages are highly vascularized. Conclusions. The presence of three vascular bundles supplying both outer and inner tepals supports their potential homology as bracteotepals. Floral vasculature also indicates that the staminodia of the fourth androecial whorl are derived from stamens. A potential homology between the stamens and appendages remains debatable, because existing evidence is contradictory.
Keywords: bracteopetals; floral development; homology; stamen appendages; staminodes; vasculature